Die bepaling van tolkakkuraatheid tydens simultane tolking by die Vrystaat Wetgewer - Liebenberg, Liezl (University of the Free State, 2003)
Abstract not available
Dissertation (M.A. (Linguistics))--University of the Free State, 2003
Keywords: Translating and interpreting -- South Africa -- Free State; Multilingualism -- South Africa -- Free State; Simultaneous interpreting -- South Africa -- Free State; Court interpreting and translating